Kegiatan Pengabdian Masyarakat: Penyuluhan Dan Edukasi Tentang Pencegahan Diabetes Melitus - Simanjuntak, Glory Gelarich (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Diabetes Mellitus (DM) is a non-communicable disease that is a global health problem and a leading cause of morbidity and mortality. Data from the International Diabetes Federation (IDF) in 2021 shows that Indonesia ranks fifth in the world for the number of diabetes sufferers. Diabetes prevention can be achieved through promotive and preventive interventions, one of which is providing community outreach and education. This Community Service (CSP) activity aims to increase public knowledge and awareness about the importance of diabetes prevention through a healthy lifestyle, early detection, and risk factor management. The activity method included interactive lectures, question-and-answer discussions, and the distribution of educational leaflets to 50 participants, consisting of productive-age and elderly residents in the activity area. Knowledge evaluation was conducted using pre- and post-tests. The results of the activity showed a 50% increase in participants' knowledge (from an average of 30% before the outreach to 80% after the outreach). Furthermore, participants demonstrated a high level of interest in adopting a healthy diet, regular exercise, and regular blood sugar checks. This activity successfully increased community understanding of diabetes prevention and can be developed into a sustainable program integrated with community health center programs and health cadres in the area.